PEMBELAJARAN TARI KIJANG UNTUK MENINGKATKAN KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN DI TK IT AL-WASIILAH KECAMATAN CIBEUREUM KOTA TASIKMALAYA - Nisa Dzurun Gola, - (2022)
This research begins with the kinesthetic intelligence abilities of children aged 5-6 years who are still not developed. This study aims to improve the kinesthetic intelligence of children aged 5-6 years through learning the deer dance. The method used to improve the kinesthetic intelligence of children aged 5-6 years in TK IT Al-Wasiilah is classroom action research (CAR) using the Kemmis and MC Taggart design model which has four stages of research consisting of planning, implementation, observation, and reflection. . The results showed that the kinesthetic intelligence of children in the first cycle was in the category of starting to develop with a percentage of 64.71%. The second cycle stage is in the category of starting to develop with a percentage of 70.58% and the category developing as expected with a percentage of 29.41%. The third cycle stage was in the category of developing as expected with a percentage of 41.18% and developing very well with a percentage of 58.82%. The kinesthetic intelligence ability of children aged 5-6 years through learning the deer dance is optimal, as can be seen from the child's ability to control movement, agile, balanced, and eye-hand-foot-head coordination. Keywords: early chilhood, kinesthetic intelligence, kijang dance lessons